Step
*
of Lemma
fun-converges-to-rsub
No Annotations
∀I:Interval. ∀f1,f2:ℕ ⟶ I ⟶ℝ. ∀g1,g2:I ⟶ℝ.
  (lim n→∞.f1[n;x] = λy.g1[y] for x ∈ I
  
⇒ lim n→∞.f2[n;x] = λy.g2[y] for x ∈ I
  
⇒ lim n→∞.f1[n;x] - f2[n;x] = λy.g1[y] - g2[y] for x ∈ I)
BY
{ (Auto THEN D 0 THEN Auto) }
1
1. I : Interval
2. f1 : ℕ ⟶ I ⟶ℝ
3. f2 : ℕ ⟶ I ⟶ℝ
4. g1 : I ⟶ℝ
5. g2 : I ⟶ℝ
6. lim n→∞.f1[n;x] = λy.g1[y] for x ∈ I
7. lim n→∞.f2[n;x] = λy.g2[y] for x ∈ I
8. m : {m:ℕ+| icompact(i-approx(I;m))} 
9. k : ℕ+
⊢ ∃N:ℕ+. ∀x:{x:ℝ| x ∈ i-approx(I;m)} . ∀n:{N...}.  (|f1[n;x] - f2[n;x] - g1[x] - g2[x]| ≤ (r1/r(k)))
Latex:
Latex:
No  Annotations
\mforall{}I:Interval.  \mforall{}f1,f2:\mBbbN{}  {}\mrightarrow{}  I  {}\mrightarrow{}\mBbbR{}.  \mforall{}g1,g2:I  {}\mrightarrow{}\mBbbR{}.
    (lim  n\mrightarrow{}\minfty{}.f1[n;x]  =  \mlambda{}y.g1[y]  for  x  \mmember{}  I
    {}\mRightarrow{}  lim  n\mrightarrow{}\minfty{}.f2[n;x]  =  \mlambda{}y.g2[y]  for  x  \mmember{}  I
    {}\mRightarrow{}  lim  n\mrightarrow{}\minfty{}.f1[n;x]  -  f2[n;x]  =  \mlambda{}y.g1[y]  -  g2[y]  for  x  \mmember{}  I)
By
Latex:
(Auto  THEN  D  0  THEN  Auto)
Home
Index